Assessment of Uterocervical Angle as a predictor of spontaneous preterm birth - Priyanka; Sangeeta Rai; Pramod Singh (Orapuh, Inc., 2024)
Introduction The changes in the "uterocervical angle (UCA)" have been reported to play a crucial role in "spontaneous preterm birth (sPTB)". Purpose The study aimed "to determine whether the UCA correlates with the risk of early 28-34 weeks and late 34-37 weeks preterm birth and assess the interobserver reproducibility of this measurement and evaluate its sensitivity as a predictor of sPTB". Methods The prospective observational study was conducted on n=50 women with singleton pregnancies of gestational age 16 to 24 weeks. In all the patients, transvaginal sonography (TVS) was performed, and UCA was noted. The ultrasound machine software was utilized for sample size determination, with a set power of 90% and α-error at 0.05 and considering findings from prior studies. To discern the variation in predictive efficacy between these two measures, a minimum sample size of 75 patients was required. Results The mean age of study subjects was 28.16±2.90 years, ranging from 23 to 34 years. Obtuse UCA >95º was seen in 47 cases, out of which 46 had PTBs. A significant difference was found between UCA when compared between the preterm and term group (102.40±4.36 vs 97.67±4.87, P<0.001). When UCA was reached within the preterm group, it found that UCA was higher in < 34-week group patients (106.25±4.13) compared to 34-37-week group patients (101.33±4.36); however, the difference was statistically insignificant (P>0.05). A significant association was found between UCA >95º and the sPTB (P<0.001). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of UCA >95º in women who delivered at <37 weeks was found to be better than other cutoffs such as UCA 95º -105º at 34-37 weeks, and ≥105º at <34 weeks. Conclusion UCA was found to be a novel ultrasound parameter that can effectively predict sPTB.